Aplikasi logika fuzzy: analisis cara kerja mesin penyedot debu menggunakan metode mamdani - Mufidah, Do’aul Isma (Maliki Interdisciplinary Journal, 2025)
Technology is increasingly developing to accompany humans who continue to develop as well. in the midst of this technological development, fuzzy logic was created. So fuzzy logic can be interpreted as fuzzy logic or logic that contains elements of uncertainty. This is a development of the previous understanding that logic has only two elements, namely false and true. One method of fuzzy logic is the mamdani method. This method is very useful in many ways, such as vacuum cleaner machines. Here, the issue is how to use the fuzzy logic Mamdani approach on a vacuum cleaner to determine the appropriate amount of suction strength to release in order to finish the job as efficiently as possible.. To apply the fuzzy method to a vacuum cleaner machine, there are several steps that must be taken, first of all determining the variables, after determining the degree of membership, then performing an inference system or fuzzy rules, and finally defuzzification using the Center of Area or Centroid method. The floor surface factor and the quantity of dust that needs to be cleaned are the elements taken into account in this study. These are the variables that will function as independents. Additionally, the machine’s projected suction power is the dependent variable. Based on data simulation with 30% input of smooth floor surface and 70% amount of dust, it will produce medium suction power of 53.7%. These results prove that based on the rule of seven that the smooth floor surface and the amount of dust will produce moderate suction power. Thus, it can be said that studies employing fuzzy logic and the Mamdani technique yield useful outcomes for vacuum cleaner use.